Study on correlation between fire fighting time and fire loss in urban building based on statistical data - Wang, Deyong; Lu, Lu; Zhu, Jiping; Yao, Jiajie; Wang, Yunlong; Liao, Guangxuan (Journal of Civil Engineering and Management, 2016)
In this paper, the correlation between fire fighting time and fire loss (burned area of urban building) based on fire statistical data in Jiangxi Province (China) from 2000 to 2010 was studied. The results showed the probability distribution of fire fighting time met lognormal distribution. In the probability density function, the expectation of the distribution represents the average level of fire fighting time. We found the average fighting time of warehouse and workshop fires were higher than the average level of whole building fires. In addition, the probability distribution of the burned area in each fire fighting time interval also followed power function, which was valid in the case of the fire fighting time within 4 hours. Furthermore, the absolute value of the exponent of the function is positively correlated with the small-scale fires and negatively with the large-scale fires. The value decreased with the increase of the fire fighting time, indicating that the fire control ability became poor with longer fire fighting time. Also, the fire control ability in residential waned fastest as the fighting time increased, and the ability in warehouse waned slowest. en fire fighting time and fire loss in urban building based on statistical data.